A New Technique for Surgical Treatment of Vaginal Agenesis Using Combined Abdominal-Perineal Approach. (6th April 2011) - Beksac, Mehmet Sinan; Salman, Mehmet Coskun; Dogan, Nasuh Utku
Abstract : Optimum therapeutic approach in vaginal agenesis has always been an area of extensive controversies. Although surgical management gained priority due to the evolution of techniques, there is currently no consensus in the literature regarding the best type of surgical approach. The most commonly preferred surgical procedure among gynecologists is McIndoe operation which involves the creation of a space between bladder and rectum, insertion of a mold covered with split-thickness skin graft into that neovaginal space, and use of postoperative vaginal dilation to avoid stenosis. However, many modifications have been introduced in time in an attempt to increase the success rates. In this paper, we describe two cases with vaginal agenesis with functioning uterus who were subjected to surgery by combined abdominal-perineal approach. The surgical technique also included the use of a specially designed vaginal mold made up of polymethyl methacrylate and use of Hyalobarrier gel which is an adhesion-preventing agent.